1967
DOI: 10.1128/jb.93.2.574-576.1967
|View full text |Cite
|
Sign up to set email alerts
|

Pathway of Glucose Fermentation in Relation to the Taxonomy of Bifidobacteria

Abstract: Cell-free extracts of 17 strains of Bifidobacterium bifidum (Lactobacillus bifidus) were examined for the presence of aldolase, glucose-6-phosphate dehydrogenase, and fructose-6-phosphate phosphoketolase. All strains turned out to lack aldolase, an enzyme unique to glycolysis, and glucose-6-phosphate dehydrogenase, characteristic of the hexosemonophosphate pathway. In all strains, fructose-6-phosphate phosphoketolase could be demonstrated. It can be concluded that bifidobacteria ferment glucose via a pathway w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(51 citation statements)
references
References 3 publications
1
50
0
Order By: Relevance
“…Thus, in cases where all of the pyruvate was cleaved rather than reduced, no lactate was formed. Because this pathway does not occur in any other species of the genus Lactobacillus, de Vries and Stouthamer (179), in agreement with some previous workers, suggested that classification of the bifidobacteria in this genus is not justified. The same alternative route of glucose dissimulation has been established in L. bifidus var.…”
Section: Biochemical Characteristicssupporting
confidence: 79%
“…Thus, in cases where all of the pyruvate was cleaved rather than reduced, no lactate was formed. Because this pathway does not occur in any other species of the genus Lactobacillus, de Vries and Stouthamer (179), in agreement with some previous workers, suggested that classification of the bifidobacteria in this genus is not justified. The same alternative route of glucose dissimulation has been established in L. bifidus var.…”
Section: Biochemical Characteristicssupporting
confidence: 79%
“…Thus, in addition to members of the Enterobacteriaceae and a number of other genera that are facultative or obligate anaerobes (for a review, see reference 21), this system is present in homofermentative lactic acid bacteria. It is absent, however, in heterofermentative lactic acid bacteria which ferment glucose via the pentose phosphoketolase pathway (4,31), or via the hexose phosphoketolase pathway (5,31). It is also absent in Z. mobilis, an anerobic pseudomonad that ferments glucose via the Entner-Doudoroff pathway (7,31).…”
Section: Uptake Of 2-deoxy-d-glucose Resting Cells Of L Casei Accummentioning
confidence: 99%
“…However, Komberg and Smith (13) were the first to emphasize the importance of the PEP yield from glycolysis, when they suggested that an Escherichia coli mutant that was defective in the EMP pathway, and was thus forced to metabolize glucose via the hexose monophosphate shunt, grew sparsely on glucose because of a deficiency in PEP required both for transport and for biosynthesis. If this line of reasoning is pursued further, one would predict that the PEP:glucose phosphotransferase system would be operative in those organisms fermenting glucose via the EMP pathway, where there is a yield of two molecules of PEP per molecule of glucose fermented, but would be absent in those organisms fermenting glucose by other pathways, such as the phosphoketolase pathway (4,5,31) or the anaerobic Entner-Doudoroff pathway (7,31), where the PEP yield is only one molecule of PEP per molecule of glucose fermented. This report shows that this prediction is realized.…”
mentioning
confidence: 99%
“…The phosphoketolase pathway ( Fig. 5A ), termed the “bifid shunt” (21) in a Bifidobacterium (22), provides an alternative to glycolysis and the pentose phosphate pathway for sugar utilization. In this pathway, the phosphoketolase enzyme splits xylulose-5-phosphate into glyceraldehyde-3-phosphate and acetyl-phosphate (23).…”
Section: Resultsmentioning
confidence: 99%